Effects of Internet-based instruction on HIV-prevention knowledge and practices among men who have sex with men - Kasatpibal,N. (Wiley-Blackwell, 2015)
© 2014 Wiley Publishing Asia Pty Ltd. HIV infection is increasing among men who have sex with men. In this study, the effects of Internet-based instruction on HIV-prevention knowledge were evaluated. The sample consisted of 162 men-who-have-sex-with-men volunteers in Thailand. The research instruments included a demographic data questionnaire, a knowledge test, and an HIV preventive practice questionnaire. The participants completed these instruments upon entry to the study and four months later. After entry to the study, the participants were given access to a previously-developed Internet-based instruction on HIV risk behaviors. Data were analyzed using descriptive statistics and paired t-test. After accessing the Internet-based instruction, the average score of HIV-prevention knowledge among the sample increased significantly, from 11.17 to 15.09 (maximum score of 20 points). The average score of practicing HIV prevention among the sample increased significantly, from 62.94 to 76.51 (maximum score of 99 points). This study demonstrated that Internet-based instruction was effective in improving HIV-prevention knowledge and practices among men who have sex with men. This suggests that Internet-based instruction could be developed for use in other countries and evaluated in a similar way.